Magnetic solid nanoparticles and their counterparts: recent advances towards cancer theranostics - Cerqueira, Mónica (2022)
Cancer is currently a leading cause of death worldwide. The World Health Organization estimates an increase of 60% in the global cancer incidence in the next two decades. The inefficiency of the currently available therapies has prompted an urgent effort to develop new strategies that enable early diagnosis and improve response to treatment. Nanomedicine formulations can improve the pharmacokinetics and pharmacodynamics of conventional therapies and result in optimized cancer treatments. In particular, theranostic formulations aim at addressing the high heterogeneity of tumors and metastases by integrating imaging properties that enable a non-invasive and quantitative assessment of tumor targeting efficiency, drug delivery, and eventually the monitoring of the response to treatment. However, in order to exploit their full potential, the promising results observed in preclinical stages need to achieve clinical translation. Despite the significant number of available functionalization strategies, targeting efficiency is currently one of the major limitations of advanced nanomedicines in the oncology area, highlighting the need for more efficient nanoformulation designs that provide them with selectivity for precise cancer types and tumoral tissue. Under this current need, this review provides an overview of the strategies currently applied in the cancer theranostics field using magnetic nanoparticles (MNPs) and solid lipid nanoparticles (SLNs), where both nanocarriers have recently entered the clinical trials stage. The integration of these formulations into magnetic solid lipid nanoparticles—with different composition and phenotypic activity—constitutes a new generation of theranostic nanomedicines with great potential for the selective, controlled, and safe delivery of chemotherapy.